Alfalfa (Medicago sativa L.) as a Promising Herbal Galactagogue for Dairy Cows: A Review - Nasihin, Ahmad (Universitas Muhammadiyah Surakarta, 2025)
Milk production in dairy cows can be enhanced through herbal-based approaches like alfalfa (Medicago sativa L.), which is known for its richness in nutrients and bioactive compounds with the potential to act as an herbal galactagogue. This study reviews scientific publications from 2015 to 2025 in the Google Scholar database to explore the use of alfalfa and its benefits for dairy cow performance. The results indicate that alfalfa can increase milk production and quality, particularly in fat, protein, and lactose content. Phytoestrogen compounds such as isoflavones and coumestrol in alfalfa stimulate prolactin hormone production and promote udder tissue growth. Phenolic compounds help improve milk yield and quality, while alkaloids enhance the milk ejection reflex. Additionally, saponins serve as defaunation agents in the rumen, increase nitrogen utilization efficiency, and support metabolic balance, positively impacting overall cow health. However, high doses of alfalfa may lead to reproductive issues due to excessive estrogenic activity, such as anestrus and infertility. The effectiveness of alfalfa also depends on factors like material quality, dosage, the cow's physiological condition, and management practices. Therefore, alfalfa should be used carefully and in balanced amounts as a functional feed to maximize benefits and prevent physiological side effects in dairy cows.